Taking action on adolescent literacy : an implementation guide for school leaders - Irvin, Judith L., 1947-; Meltzer, Julie, 1963-; Dukes, Melinda S., 1971- (Alexandria, Va. : Association for Supervision and Curriculum Development, 2007)
Provides a leadership plan and action steps that will build on students' literacy skills and intervene with students who falter. Includes strategies to integrate literacy and learning across the content areas; support structures that involve teachers, administrators, parents, and community members in your literacy program; and examples of school environments that sustain literacy development.
Student motivation, engagement, and achievement -- Integrating literacy and learning : across the content areas -- Integrating literacy and learning : interventions for struggling readers and writers -- Sustaining literacy development : school, parent, community, and district support -- Develop and implement a schoolwide literacy action plan -- Support teachers to improve instruction -- Use data to make decisions -- Build leadership capacity -- Allocate resources.
Includes bibliographical references (pages 253-261) and index.
Print version record.
Keywords: Reading (Middle school) -- United States; Reading (Secondary) -- United States; Language arts (Middle school) -- United States; Language arts (Secondary) -- United States; LANGUAGE ARTS & DISCIPLINES -- Reading Skills; Language arts (Middle school); Language arts (Secondary); Reading (Middle school); Reading (Secondary); United States; Electronic books; Electronic books